Methodology and Computing in Applied Probability - Glaz, Joseph; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Methodology and Computing in Applied Probability will publish high quality research and review articles in the areas of applied probability that emphasize methodology and computing. Of special interest are articles in important areas of applications that include detailed case studies. Applied probability is a broad research area that is of interest to many scientists in diverse disciplines including: anthropology, biology, communication theory, economics, epidemiology, finance, linguistics, meteorology, operations research, psychology, quality control, reliability theory, sociology and statistics. The following alphabetical listing of topics of interest to the journal is not intended to be exclusive but to demonstrate the editorial policy of attracting papers which represent a broad range of interests: Algorithms Approximations Asymptotic Approximations & Expansions Combinatorial & Geometric Probability Communication Networks Extreme Value Theory Finance Image Analysis Inequalities Information Theory Mathematical Physics Molecular Biology Monte Carlo Methods Order Statistics Queuing Theory Reliability Theory Stochastic Processes.
Keywords: Business; Management science; Life sciences; Statistics; Electrical engineering; Economics; Statistics, general; Life Sciences, general; Electrical Engineering; Economics, general; Business and Management, general